Unemployment Dynamics in Indonesia: A Statistical Review and Policy Implications in Sharia Economic Perspectives - Juita, Risa; Arum, Hafidza Sanshia (MUI Kota Pekanbaru, 2025)
This study analyzes the open unemployment rate (OUR) in Indonesia as of August 2024 by using official data published by the Central Statistics Agency (BPS). The national OUR stood at 4.91%, with approximately 7.48 million unemployed individuals from a workforce of 152.11 million people. Regional disparities remain apparent, especially in West Java with a higher OUR of 6.75%. Factors influencing unemployment include education quality, regional minimum wages, inflation, and unequal investment distribution. From a sharia economic perspective, unemployment is not only an economic issue but also a matter of social justice and moral responsibility. Islam emphasizes work as a form of worship and the foundation of community welfare. Therefore, this study highlights the relevance of integrated and inclusive employment policies—emphasizing skills development, just wage systems, and equitable access to employment opportunities—while promoting the potential of Islamic social finance instruments such as productive zakat, cash waqf, and qardhul hasan. The findings are expected to serve as a valuable reference for policymakers to design sustainable, fair, and faith-aligned strategies for reducing unemployment and improving labor quality in Indonesia.